Play and toys as cultural tools and practices: A comparative study - (:unkn) unknown (IGI Global, 2018)
Culture can be defined as the set of beliefs, traditions, values, customs, and norms specific to a group of people; it is acquired through the socialization process and is dominant and effective in all of our daily practices. Culture refers to the traditions and values of our communities, and through play, children explore and learn the rules and symbols of their communities. People of each generation, as they engage in sociocultural endeavors with other people, make use of and extend cultural tools and practices inherited from previous generations. This chapter aims to compare the use of two historical toys in two different cultures as cultural tools ("Eyüp Toys" and "Nuremberg Toys"); two activities in two different cities as cultural practices ("World Play Day" activities in Istanbul and the Toys Fair in Nuremberg); and finally, two institutions in two different cities as cultural institutions (Ataşehir Municipiality Düştepe [Dreamhill] Game Museum in Istanbul and Toy Collection at Germanisches Nationalmuseum in Nuremberg). © 2018, IGI Global. All rights reserved.